APLIKASI TEKNIK Polymerase Chain Reaction (PCR) UNTUK MENDETEKSI PEMALSUAN BAKSO SAPI YANG DICAMPUR DENGAN DAGING TIKUS - , ASTRI NUR FAIZAH; Dr. drh. Yatri Drastini, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Food is meant for human consumption therefore the origin of the food is very essential. Processed food, such as meatball, is often adulterated by mixing ground beef with rat meat. Rat meat is cheaper and easier to find than any other animal. Unfortunately, rat meat status is haram for Moslem and dangerous for human health because of its unknown origin. Food adulterated with rat meat threatens food safety in public markets. Therefore, PCR technique is applied for detecting rat meat as additional meat. In this research, material used were meats from three kinds of rat (Rattus rattus, Rattus norvegicus, and Mus musculus), ground beef, and also mixed beef + rat meatball. Workflow in this research was implemented first by isolating DNA using DNeasy kit, calculating concentration and DNA purity by spectrophotometer, then amplifying target sequences by PCR using rat specific primer rRNA 16S as detector. Results of PCR products were visualized by electrophoresis. Polymerase Chain Reaction product size for rat primer is 493 bp. Result showed that the only rat detected was Rattus norvegicus or also known as albino rat. Rattus rattus and Mus musculus could not be identified by rat primer used in the research. As for processed food product, rat could not be detected in the meatball.